THE URGENCY OF MEDICAL MARIJUANA LAWS IN INDONESIA - Haque, Amarta Yasyhini Ilka; Susila, Muh Endriyo (Diponegoro Law Review, 2024)
Marijuana legalization remains a contentious public health issue in Indonesia. Despite public debates sparked by a mother's appeal for medicinal marijuana last June, Indonesia maintains strict anti-drug measures under its Narcotics Law, which prohibits the use of all elements of marijuana in medical treatments. However, medicinal marijuana has gained recognition in other jurisdictions for its potential to treat various chronic illnesses. This study employs a doctrinal legal research methodology, relying on secondary sources, legislation, and scholarly analyses. The findings emphasize the urgent need to legalize medicinal marijuana as a critical intervention for specific medical conditions. While possession and use of marijuana remain illegal, Indonesia's ratification of the Single Convention on Narcotic Drugs 1961 allows for research and the controlled use of medicinal marijuana. By examining the experiences of nations with established medical marijuana legislation and emphasizing further research on its applications, this study advocates for the legalization of medicinal marijuana in Indonesia under stringent regulations.